UNILATERAL CMV RETINITIS IN HIV/AIDS PATIENT WITH MULTIPLE OPPORTUNISTIC INFECTIONS: Poster Presentation - Case Report - Resident - Bening, Daya Banyu; Firmansjah, Muhammad; Zuhria, Ismi; Yustiarini, Ima; Widjaja, Sauli Ari (Majalah Oftalmologi Indonesia, 2023)
Introduction : CMV Retinitis is the most common opportunistic infection in HIV/AIDS patient. Ocular manifestations in HIV/AIDS have similar clinical features though the management therapies are different. Case Illustration : A 47-year-old man was presented with blurred vision on LE since 4 months. Patient was diagnosed with HIV/AIDS since 2 years. Patient only had light perception on LE, and 5/10 on RE. The LE anterior segment showed flare and cell indicating active anterior uveitis. The LE posterior segment revealed extensive hemorrhage and exudate known as ‘pizza pie’ appearance, and cotton wool spot with multiple ischemic areas on RE. Laboratory tests revealed reactive IgG CMV and very low CD4 count (4 cell/?l). Patient was also diagnosed with Tinea Corporis, Scabies, and Pneumocystis carinii pneumonia. Oral Valganciclovir 900 mg was administered twice a day for 3 weeks, along with anti- retroviral therapy. Discussion : The anterior uveitis and ‘pizza pie’ appearance with positive CMV IgG indicate CMV Retinitis in fulminant form. Cotton wool spot found in the RE leads to retinal microvasculopathy due to HIV invading the vascular endothelium and causing increased plasma viscosity. This patient only had 4 cell/?l CD4 which indicates severe immune deficiency. If not treated immediately, patients with CD4 count <50 are at higher risk of contralateral eye involvement. Oral Valganciclovir was chosen considering the multiple opportunistic infections the patient had. Conclusion : It is important to distinguish CMV retinitis with other HIV/AIDS ocular manifestations. The choice of therapy needs be considered with the overall condition of patient.